Plasma Waves Around Massive Stars in (3+1)-General Relativistic Magnetohydrodynamics - Shokrgozar Arani, Hassan; Abarghouei Nejad, Salman [UNESP]; Talaei Faghloo, Mahtab; Ramezani Arani, Reza (Springer Nature, 2022)
In this article, the propagation of plasma waves around rotating and non-rotating stars is studied in a TPM (Thorne-Price-Macdonald) (3+1)-general relativistic magnetohydrodynamics (GRMHD) formalism. For more simplicity, the plasma around the atmosphere of the stars is considered to be stationary. Using WKB approximation, we derive the local longitudinal and transverse dispersion relations and compare them to the special relativistic congener.
Keywords: One-fluid plasma equations; Plasma waves dispersion equations; Plasma waves propagation equations; TPM (Thorne-Price-Macdonald) (3+1)-general relativistic magnetohydrodynamics; WKB approximation